RELATIONSHIP OF MOM'S KNOWLEDGE ABOUT TOILET TRAINING WITH MOM'S BEHAVIOR IN TOILET TRAINING IN TODDLER AGE CHILDREN - Eka Falentina Tarigan; Siti Nurmawan Sinaga; Eva Ratna Dewi (International Journal of Midwifery Research, 2022)
The literature report conducted in Singapore in 2000 showed that 15% of children continued to wet the bed after 5 years of age and about 1.3% of boys and 0.3% of girls in Indonesia still had the habit of urinating and defecating indiscriminately. age 7 years, this is due to failure in toilet training. Failure to toilet training can cause a child to experience enuresis or bedwetting. This study aims to determine whether there is a relationship between maternal knowledge about toilet training and mother's behavior in toilet training for toddlers in the Panei Tongah health center, Simalungun district in 2021. This research was a cross sectional analytical survey research. The sample in this study amounted to 33. The sampling technique used in this study used purposive sampling. The 33 respondents, mothers with good knowledge about toilet training had good behavior in training toilet training for toddler age children, namely 20 people (60.6 %). And based on the results of the bivariate test, the p value = 0.002 means p value > 0.05 so it can be concluded "There is a relationship between mother's knowledge about toilet training and mother's behavior in training toilet training in toddler age children. It is hoped that PMB leaders as health workers need to further increase mother's knowledge about toilet training, its impact and benefits so that mother's knowledge will increase about toilet training.